1973
DOI: 10.1139/v73-235
|View full text |Cite
|
Sign up to set email alerts
|

Metal Complexes as Antioxidants. I. The Reaction of Zinc Dialkyldithiophosphates and Related Compounds with Peroxy Radicals

Abstract: The kinetics of the inhibition of the autoxidation of several hydrocarbons by a number of zinc dialkyldithiophosphates and by zinc isopropylxanthate and zinc diethyldithiocarbamate have been studied at 30' and at 50'. The oxidations were generally auto-retarding but initial rate measurements showed that these compounds trapped peroxy radicals and allowed rate constants for this process to be calculated. Rate constants for the reaction of t-butylperoxy radicals with these compounds have been measured by a kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(22 citation statements)
references
References 10 publications
(17 reference statements)
1
21
0
Order By: Relevance
“…lrradiation of either a sensitizer-free solution of 3-methyl-2-pentene in chlorobenzene or an olefin-free solution of tetraphenylporphine in chlorobenzene yielded no detectable hydroperoxide ( 4 x M ) . Many metal chelates are rapid decoinposers of hydroperoxides (6,16). However, separate dark experiments with oxidized 3-methyl-2-pentene solutions showed that the hydroperoxide concentrations did not decrease either in the presence of nickel(I1) [2,2'-thiobis-4-(I, l,3,3-tetramethylbuty1)phenolate]-12-butylam~ne or of the sensitizer.…”
Section: Photochemical '0 Generatio~zmentioning
confidence: 99%
“…lrradiation of either a sensitizer-free solution of 3-methyl-2-pentene in chlorobenzene or an olefin-free solution of tetraphenylporphine in chlorobenzene yielded no detectable hydroperoxide ( 4 x M ) . Many metal chelates are rapid decoinposers of hydroperoxides (6,16). However, separate dark experiments with oxidized 3-methyl-2-pentene solutions showed that the hydroperoxide concentrations did not decrease either in the presence of nickel(I1) [2,2'-thiobis-4-(I, l,3,3-tetramethylbuty1)phenolate]-12-butylam~ne or of the sensitizer.…”
Section: Photochemical '0 Generatio~zmentioning
confidence: 99%
“…Now, the formation of the phenoxy radical is well interpreted by the proposal that a complex can decompose cumyl hydroperoxide homolytically by the sulfur-containing chelate ring as reported by Burn et al2), (1) and the resulting cumyloxy (or cumyl peroxy) radical reacts immediately with the phenolic moiety contained in the complex to give the phenoxy The g-values and splitting constants (a) of ESR signals for phenoxy radicals are shown in Table 3. The triplet-triplet splitting is ascribable to coupling with protons of -CH2-on para position and mhydrogen.…”
Section: Esr Spectramentioning
confidence: 79%
“…Zinc diisopropyldithiophosphate, nickel diisopropylor stable free-radical (2, 3). Moreover, these radi-dithiophosphate, zinc diethyldithiocarbamate, nickel diethylcals may initiate hydrocarbon autoxidation, induce dithiocarbamate, and nickel di-n-butyldithiocarbamate had been hydroperoxide decomposition, and give rise to the prepared previously in our laboratory (4)(5)(6). tert-Butyl hydroperoxide, cumene hydroperoxide, diisopropyldithiophosphoryl chemiluminescence with autoxi-disulphide.…”
Section: Introductionmentioning
confidence: 85%
“…Application of the usual steady-state assumptions indicates that the rate of disappearance of 2 should be given by [4].…”
Section: Preliminary Experimentsmentioning
confidence: 99%
See 1 more Smart Citation